Global Social Policy in Achieving Sustainable Development Goals - Dr.U.Sarangi (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2021)
The research paper entitled ―Global Social Policy in Achieving Sustainable Development Goals’ aims to study the concepts of universal health coverage(UHC), social protection floor approaches that determine the global health agenda. The paper also highlights certain aspects such as the role of WHO in determining the global health agenda, assessing inequalities in health systems of national economies and in adopting corrective measures to reduce them. The paper also dwells into the study of the role of various other global institutions such as United Nations, UNRISD, ILO, OECD, World Bank, IMF etc., which govern global social policy through various interventions such as the SDGs, sustainable development performance indicators, social solidarity enterprise(SSE), sustainable livelihoods framework, social value international‘s social return on investment, financing SSE etc., The global issues that are covered at length include policy coherence to achieve UHC, persistent global inequities challenge the achievement of UHC, social protection floors(SPFs) as a strategy to address inequities i.e. universal social protection schemes & systems, policy coherence through whole-of-government approaches involving high-level policy coordination globally, nationally, sectorally and sub-nationally, achieving policy coherence and coordination, definition of SSE, initiatives linked to the SSE sector, evaluation of social usefulness, balance social, measuring impact as a burden for SSE organizations, standard global policy issue in times of COVID-19, achieving SDG-10 through Public Service Inclusion Strategies for Ethnic and Religious Minorities, global social policy formulation, social policy making process, global institutions, challenges facing global institutions in shaping global social policy and way forward among others. The paper analyzes the fact that National social policy is not only relevant but also helps in the design of global social policy. In order to evaluate the roles played by global institutions and there inter-linkages with that of global social policy, it is pertinent to look at how fair and amenable the national social policy is to global social policy. This means that as long as one can understand global social policy by looking at national social policy, one also can understand national social policy by looking at global social policy. The regional social policy also matters and has a vital role to play though not directly, but by influencing national social policy in the long run and need to be taken into account while assessing the role of national social policy in global governance. Therefore, the national, regional and global institutions are all interrelated and interdependent and in turn affect the global social policy in the long run